Heat-Labile Antigens of Salmonella enteritidis II. Mouse-protection Studies - Collins, F. M. (1966)
Collins, F. M. (University of Adelaide, Adelaide, South Australia), and Margaret Milne. Heat-labile antigens of Salmonella enteritidis. II. Mouse-protection studies. J. Bacteriol. 92:549–557. 1966.—A number of extracts prepared from a virulent and an avirulent strain of Salmonella enteritidis were used to immunize mice. Living and alcohol-killed whole-cell vaccines were also used to compare the relative protective value of the various preparations. All mice were challenged intravenously with 100 to 1,000 ld(50) of S. enteritidis. Daily counts of the liver, spleen, and blood populations of vaccinated and control mice revealed that the challenge organism was rapidly eliminated only in those mice which had been immunized with a living vaccine. Immunization with extracts resulted in rapid clearance of S. enteritidis from the blood, but, after a delay of 24 to 48 hr, the bacterial populations increased until a maximal liver and spleen population of approximately 5 × 10(8) was reached. Between 55 and 100% of the immunized animals died, compared with 95 to 100% of the controls. With all four extracts, it was only the first antigenic fraction eluted from diethylaminoethyl cellulose which had any detectable effect on host resistance. The ineffectiveness of vaccines prepared with the various extracts or with whole killed bacteria relative to the protection observed after immunization with living organisms is discussed.